Edukasi Kader Kesehatan dalam Rangka Pelaksanaan Skrinning Diabetes Melitus Tipe 2 di Puskesmas Pengasinan Kota Depok - Permatasari, Putri; Setiawati, Marina Ery (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
Health cadres are members of the community who play a role in the health sector so that the community has an awareness to live a healthy and clean life. A healthy lifestyle is an effort to reduce the risk factors for non-communicable diseases (NCDs). Health cadres also need to provide education to the community. To be able to do this, health cadres need to receive training and assistance in implementing health education regarding risk factors for non-communicable diseases. The purpose of this activity is to increase the knowledge of health cadres through training and assistance in providing health education to the community. Method. The stages of this activity consist of the first: preparation including making modules, permits for implementing activities, health screening, initial meetings with health cadres, Second stage: Implementation of training, the first day of providing modules and explaining the contents of the modules, pretests and posttests are carried out. On the second day, a health education simulation is carried out using flipchart media. Third stage: application of health education to the community who have one or more risk factors for non-communicable diseases. This stage is carried out by filling out a questionnaire before and after health education is carried out. The results of this community service activity are the response and responsiveness of cadres and the community in providing type 2 Diabetes Mellitus Education in the Pengasinan Health Center area. Based on the results of this activity, for training activities, the average knowledge of cadres before training was 58% and increased to 87.5% after training. The average value for simulation was 74.32 (good). For community knowledge, out of 5 indicators with values, 4 showed a difference in knowledge before and after being given education by health cadres, only 1 showed no difference. Conclusion. This activity shows an increase in cadre knowledge after being given training and the influence of education provided by health cadres on community knowledge. In the future, activities like this need to be improved again and can encourage increased screening for Type 2 DM in this activity area.